Prevalence of Overweight and Obesity and Association with Risk Factors in Secondary School Children in Croatia - Antonela Matana; Helena Krajinović (Children)
Background: Childhood and adolescent overweight and obesity represent significant global health concerns. The primary objective of this study was to assess the prevalence and associations of some potential risk factors with overweight and obesity among Croatian adolescents aged 15 to 18. Methods: This cross-sectional study included 344 secondary school students from Croatia’s Mediterranean region, with data collected through an anonymous questionnaire. The questionnaire gathered sociodemographic information, adherence to the Mediterranean diet of both children and their parents, and the children’s dietary habits and physical activity levels. Results: Weight status data revealed that 2.6% of participants were underweight, 82% had normal weight, 11% were overweight, and 4.4% were classified as obese. The results indicated that boys (p < 0.001), children who skip breakfast (p = 0.031), those with less active lifestyles compared to their peers (p = 0.001), children whose mothers have a higher BMI (p < 0.001), and children from smaller families (p = 0.034) are at greater risk of being overweight or obese. Conclusions: This study provides valuable insights into the risk factors associated with overweight and obesity in this age group, which can support the development of targeted strategies for this population.